Cell death offers exceptional cellular and molecular windows for pharmacological interventions in protozoan parasites. Issue 2 (2017) - El-Ashram, Saeed; Nasr, Ibrahim Al; mehmood, Rashid; Çağdaş, Dincel; Hu, Min; He, Li; Suo, Xun
No abstract available